A Study in Viscosity and Clotting of Blood in Haemophiliacs* - Dintenfass, L; Castaldi, P (Thrombosis and Haemostasis, 1964)
Viscosity and clotting of blood were studied an a series of eight haemophilic (Factor VIII deficiency) patients. A cone-in-cone rotational viscometer was employed. Viscosity was determined over a range of rates of shear (0.04- 100 sec-1). Blood was found to be thixotropic, but great variations were observed between the individual cases. The extreme difference in viscosity between the severe and the mild haemophiliacs was 20-fold.A tendency was observed for the clotting time to decrease with an increase in the velocity gradient. Clotting time was found also to decrease with an increase in temperature if determined at high rates of shear.